Data Integration Framework for Heterogeneous System Landscapes Within the Digital Factory Domain - Himmler, Florian; Amberg, Michael (24th DAAAM International Symposium on Intelligent Manufacturing and Automation, 2013)
Due to shorter product lifecycles and a rising complexity of the products more and more enterprises consider using the Digital Factory. The Digital Factory is an IT system capable of digitally planning, controlling and optimizing all resources and activities related to a product which are performed beginning with product development and ending in the order processing – prior to the start of the real production of the product. Today the companies’ system landscapes within the Digital Factory domain are usually very heterogeneous with limited interoperability of the applications in use. However data integration is crucial for a successful implementation of the Digital Factory. This article provides a reference model based framework consisting of three main steps and ten sub-steps. It can be applied by companies in order to optimize and integrate such heterogeneous system landscapes